RANCANG BANGUN APLIKASI PENCATATAN PENJUALAN KONSINYASI PADA PT.SEMESTA NUSTRA DISTRINDO - Anggraeni, Dyah Ayu; Arifin, Mochammad; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT . Semesta Nustra Distrindo is a trading company that sells an assortment of biscuits and snacks . The Company is conducting the sale in the form of consignment sales . Consignment sales done entrust the goods to the buyer / outlet which acts as a sales agent . The company currently experiencing problems when consignment sales .To overcome the problems faced by PT . Semesta Nustra Distrindo then made design registration applications consignment sales .With this application, recording consignment sales at PT. Semesta Nustra Distrindo can simplify and solve the problems in the process of consignment sales at PT . Semesta Nustra Distrindo. With this application can help companies in consignment sales and consignment sales can generate reports , billing statements , payment reports , and sales schedules based on time and location specified.